Competing and Learning in Global Value Chains: Firms’ experiences in the case of Uganda A study of five sub-sectors with reference to trade between Uganda and Europe - Wiegratz, Jörg; Nyabuntu, Paschal; Omagor, Charles (White Rose Research, 2007)
The evolution and sophistication of cross-border, value-adding networks of global production and trade in both goods and services is one of the key characteristics of global markets. The analysis of the underlying structures and processes of this global fragmentation, relocation, and coordination of economic activities becomes vital for developing country‟ entrepreneurs and policy makers who face respective challenges and opportunities in their efforts to integrate firms into the global economy in a competitive and beneficial manner. In this context, the study of Global Value Chains (GVCs) becomes relevant. A value chain (VC) describes the full sequence of discrete value-added activities needed to bring a specific product/service from its conception through the different stages of production to its use and final disposal after use. The activities that comprise a VC can be contained in a single firm or strategically divided among several firms. In GVCs, activities are divided among multiple firms and spread across wide geographic spaces. The analysis of GVCs focuses on (1) the global dispersion of different value-added activities in product specific VCs and (2) on the related upgrading possibilities - in terms of products, processes, functions and sectors - for local firms. A main concern of research is (3) the analysis of inter-firm relationships and interactions in GVCs; in particular, the way in which the lead (or key) firm of a GVC governs (organizes, coordinates, and controls) the activities and inputs of the firms participating at different functional positions in the upstream GVC part (e.g. up to farmers).